Diagnosis and characterization of mania: Quantifying increased energy and activity in the human behavioral pattern monitor. (30th June 2016) - Perry, William; McIlwain, Meghan; Kloezeman, Karen; Henry, Brook L.; Minassian, Arpi
Abstract: Increased energy or activity is now an essential feature of the mania of Bipolar Disorder (BD) according to DSM-5. This study examined whether objective measures of increased energy can differentiate manic BD individuals and provide greater diagnostic accuracy compared to rating scales, extending the work of previous studies with smaller samples. We also tested the relationship between objective measures of energy and rating scales. 50 hospitalized manic BD patients were compared to healthy subjects (HCS, n =39) in the human Behavioral Pattern Monitor (hBPM) which quantifies motor activity and goal-directed behavior in an environment containing novel stimuli. Archival hBPM data from 17 schizophrenia patients were used in sensitivity and specificity analyses. Manic BD patients exhibited higher motor activity than HCS and higher novel object interactions. hBPM activity measures were not correlated with observer-rated symptoms, and hBPM activity was more sensitive in accurately classifying hospitalized BD subjects than observer ratings. Although the findings can only be generalized to inpatient populations, they suggest that increased energy, particularly specific and goal-directed exploration, is a distinguishing feature of BD mania and is best quantified by objective measures of motor activity. A better understanding is needed of the biological underpinnings of this cardinal feature. Highlights: Increased activity/energy is now a required symptom for a manic episode in DSM-5. Higher goal-directed specific exploration distinguishes mania of bipolar disorder. Quantifying motor activity yields higher sensitivity than clinical rating scales.